Comparative effectiveness of early rhythm control versus rate control for cardiovascular outcomes according to sex in patients with atrial fibrillation. (19th May 2022) - Yang, PS; Kim, DH; Jang, E; Yu, HT; Kim, TH; Pak, HN; Lee, MH; Sung, JH; Joung, B
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministry of Health & Welfare, Republic of Korea Background: Rhythm control is associated with better cardiovascular outcomes than usual care among patients recently diagnosed with atrial fibrillation (AF). However, there are limited data on the outcomes of AF ablation according to sex. The purpose of this study was to evaluate gender differences in the effects of early rhythm control compared to rate control on the primary composite outcome of cardiovascular death, ischaemic stroke, hospitalisation for heart failure (HF), or myocardial infarction. Methods: We conducted a retrospective population-based cohort study including 22635 patients with AF newly treated with rhythm control (antiarrhythmic drugs or ablation) or rate control in 2011-2015 from the Korean National Health Insurance Service database. Propensity overlap weighting was used. Results: Among patients with early AF treatment (initiated within 1 year since diagnosis), compared with rate control, rhythm control was associated with a similar lower risk of the primary composite outcome both women (weighted incidence rate per 100 person-years: 8.68 in rhythm control vs. 10.3 in rate control; hazard ratio [HR] 0.79, 95% confidence interval [CI] 0.69 to 0.90; P<0.001) and men (weighted incidence rate per 100 person-years: 6.33 in rhythm control vs. 8.32 in rate control; HR 0.77, 95% CI 0.67 to 0.88; P<0.001). However, the effective initiation time for rhythm control therapy was within 6 and 11 months after AF diagnosis in female and male patients, respectively. Moreover, the effective times for other outcomes were different between genders (hospitalization for HF; female within 2 months, male within 9 months/ ischemic stroke; female within 11 months, male immediately). Conclusions: Early initiation of rhythm control was associated with a lower risk of primary outcome in both genders. However, the effective rhythm control treatment initiation time for primary outcome, stroke and HF-related admission was different in both genders. For rhythm control treatment to be effective, women should start treatment earlier than men.